Directly integrated mixed‐dimensional van der Waals graphene/perovskite heterojunction for fast photodetection - Xiangshun Geng; Peigen Zhang; Jun Ren; Guan‐Hua Dun; Yuanyuan Li; Jialun Jin; Chaolun Wang; Xing Wu; Dan Xie; He Tian; Yi Yang; Tian‐Ling Ren (InfoMat, 2022)
Abstract Mixed‐dimensional (2D/3D) van der Waals (vdW) heterostructures made with complementary materials hold a lot of promise in the field of optoelectronic devices. Beyond simple mechanical stacking, directly growing the single‐crystal perovskite on 2D materials to construct a high‐quality vdW heterojunction can better promote carrier transport. In this work, a monolithic integrated graphene/perovskite heterojunction device is fabricated by directly growing a single‐crystal hybrid perovskite on monolayer graphene. Due to the strong interface coupling, the hybrid device achieves self‐powering behavior and exhibits prominent photoresponse properties with a fast response speed of up to 2.05 μs. Moreover, the responsivity and detectivity can be boosted to up to 10.41 A W−1 and 4.65 × 1012 Jones under the actuation of −3 V bias. This technique not only improves the device performance, but also provides an effective guideline for the development of next‐generation directly integrated vdW optoelectronic devices.